Modelling chloride diffusion in concrete with influence of concrete stress state - Wang, Jian; Ng, Pui-Lam; Wang, Weishan; Du, Jinsheng; Song, Jianyong (Journal of Civil Engineering and Management, 2017)
Under coastal or marine conditions, chloride erosion is the major accelerating factor of reinforcement corrosion. Therefore, it is of vital importance to investigate the chloride diffusion model. Research reveals that the concrete stress state has great influence on chloride diffusion; therefore a stress influence coefficient was incorporated in chloride diffusion coefficient model by many researchers. By referring to the experimental data from eight different researchers, the law between stress influence coefficient and concrete stress ratio is studied in detail, and equations relating the stress influence coefficient with the concrete stress ratio are established. Compared with three typical existing groups of equations, it is found that the proposed equations give the most accurate estim.ation of the stress influence coefficient. Hence, the proposed equations can be adopted to improve the valuation of chloride diffusion coefficient, and a modified chloride diffusion model is put forward. Three groups of experimental data are used to validate the modified chloride diffusion model, which is shown to be reasonable and having high prediction accuracy.